2007
DOI: 10.1128/aac.01096-06
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Antiassociation Activity of Translation Initiation Factor 3 by Paromomycin

Abstract: The effect of paromomycin on the interaction of ribosomal subunits was studied. Paromomycin inhibited the antiassociation activity of initiation factor 3 (IF3). Furthermore, ribosomal subunits were associated to form 70S ribosomes by paromomycin even in the presence of 1 mM Mg 2؉ . Paromomycin did not inhibit the binding of IF3 to the 30S ribosomal subunits. On the other hand, IF3 bound to the 30S subunits was expelled by paromomycin-induced subunit association (70S formation). These results indicate that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…[However, we have also observed that, at least in most cases, paromomycin can be omitted from the medium for ≥2 wk without affecting the levels of GOI expression observed, an approach that may often be desirable given the known effects of paromomycin in decreasing the fidelity of translation (Davies et al 1965; Mironova et al 1982; Hirokawa et al 2007). ] Moreover, if a particular GOI fails to express efficiently for any reason, the number of transformants obtained would simply drop, saving the investigator from screening hundreds of colonies for a nonexistent GOI-expressing clone.…”
Section: Discussionmentioning
confidence: 91%
“…[However, we have also observed that, at least in most cases, paromomycin can be omitted from the medium for ≥2 wk without affecting the levels of GOI expression observed, an approach that may often be desirable given the known effects of paromomycin in decreasing the fidelity of translation (Davies et al 1965; Mironova et al 1982; Hirokawa et al 2007). ] Moreover, if a particular GOI fails to express efficiently for any reason, the number of transformants obtained would simply drop, saving the investigator from screening hundreds of colonies for a nonexistent GOI-expressing clone.…”
Section: Discussionmentioning
confidence: 91%
“…3A, boxed nucleotides) (14) and stimulates ribosome subunit association at low-magnesium ion concentrations (15). We hypothesized that binding by paromomycin might shift the equilibrium of the 16S rRNA from the inactive to the active state.…”
Section: Resultsmentioning
confidence: 99%
“…PAR inhibited all three reactions of the disassembly process (Figure 5A–C). In addition, it re-associated yeast ribosomal subunits (Figure 5D) as it did the bacterial ribosomal subunits (31). This suggested that it acts like Mg 2+ , but this was disproven by the experiment shown in Figure 5E, demonstrating that the inhibitory effect of PAR on the disassembly reaction was not significantly influenced by Mg 2+ .…”
Section: Resultsmentioning
confidence: 88%